Um resgate à geometria descritiva - Lira, Francisco Misael Albuquerque (2022)
The work aims to present a study on descriptive geometry, award its importance in the development of the student's spatial vision. are initially Briefly, postulates, theorems, designed to space, straight lines and geometry planes, as a form of theoretical foundation for the reader. In Next, we present studies of projections, their elements and projections as conics and ci, which are a basis for the double configuration method or togonal or monk method. Created by Gaspar Monge was injured and formalized a technique for it to be done Three-dimensional figures in two-dimensional planes to project what we call epura, material that revolutionized the time in both engineering and design areas. Finally, we present applications of descriptive geometry in different areas of study, design of architecture, cartography, as well as an idea of ​​a study approach in the 3rd year of this teaching medium, with the objective of increasing and improving the student's visual ability.